Childhood and the armed conflict in Colombia from the perspective of films and education - Téllez-Gómez, Angie Alejandra; Cárdenas-Obregón, Karen Andrea (Uptc, 2021)
The objective of this article is to reflect on the armed conflict in Colombia and the relationship between children and adolescents and how it is viewed from an educational perspective through the analysis of four Colombian films that portray violence. In addition to some theoretical foundations, the films were approached methodologically from the concept-image, which consists of being affected by an experience and/or transmitted emotional impact, leading to the consolidation of different visions and points of view of the world through films. There is an additional emphasis on the relationship of cinema as a resource for teaching and learning. On one hand, it is used as a way to project reality and on the other, it is used as a method of research inside and outside of the classroom. This is due to the fact that films allow us to get closer to childhood from the perspective of the armed conflict in Colombia and to demonstrate its impact on childhood and therefore, on society.